2020
DOI: 10.3390/ijerph17249585
|View full text |Cite
|
Sign up to set email alerts
|

New Multilevel Partnerships and Policy Perspectives on Active Ageing in Italy: A National Plan of Action

Abstract: Active ageing (AA) policies aim to improve quality of life of older people by enabling better social participation and inclusion. Despite many international initiatives to promote AA undertaken in recent years, Italy did not systematically address this policy challenge until very recently. This paper presents the first national Plan-of-Action (PoA) (2019–2022) adopted by this country for supporting policy design and recommendation in this field. The PoA aims to create a multilevel, co-managed coordination of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 16 publications
0
37
0
Order By: Relevance
“…The increasing trends indicated that current strategies were still ill-prepared for the population aging. The findings indicated that active strategies should be adopt to cope with the problems caused by PD, including healthcare and security systems, civil health promotion plan, and healthy lifestyle (66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…The increasing trends indicated that current strategies were still ill-prepared for the population aging. The findings indicated that active strategies should be adopt to cope with the problems caused by PD, including healthcare and security systems, civil health promotion plan, and healthy lifestyle (66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the call for more customized PA interventions for people experiencing the retirement transition [ 1 , 107 ]. While policy making may benefit from these results, research suggests that top-down policy making in active ageing issues should be avoided, and that to apply a codecisional model involving all the relevant stakeholders may be useful [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, QoL differs between individuals and contexts. Differences in culture, living conditions, healthcare resources and policies have a measurable effect on how European citizens age [8,10]. In fact, reports have described differences in the distribution of ageing conditions such as multimorbidity or frailty across European countries, with marked north/south and east/west gradients [11,12].…”
Section: Introductionmentioning
confidence: 99%